The Reciprocal Relationship between Suicidality and Stigma - Carpiniello, Bernardo; Pinna, Federica (Frontiers in Psychiatry, 2017)
Introduction: Although suicidality is frequently the cause of stigma, it is conversely true that stigma may be the cause of suicidality. The present paper focuses on the complex relationships that exist between suicidal behaviour and stigmatizing attitudes. Methods: a narrative review of the topic will be presented on the basis of the relevant literature collected from an electronic search of PubMed, ISI Web of Knowledge and Scopus databases, sing stigma, public stigma, structural stigma, perceived stigma, self-stigma, suicide, attempted suicide, suicidality as key words. Results: a negative perception is frequently held of suicidal people, labelling them as weak and unable to cope with their problems, or selfish. Individuals who have attempted suicide are subject to similar processes of stigmatisation and "social distancing"; insurance policies include an exclusion clause against death by suicide. Subjects with a direct personal experience of depression or suicide strongly endorse a feeling of self-stigma; those who have attempted suicide are often ashamed and embarrassed by their behavior, and tend to hide the occurrence as much as possible. Similar processes are observed amongst family members of subjects who have committed suicide or made a suicide attempt, with a higher perceived stigma present in those bereaved by suicide. Perceived or internalized stigma produced by mental or physical disorders, or through belonging to a minority group, may represent a significant risk factor for suicide, being severely distressing, reducing self-esteem and acting as a barrier in help-seeking behaviours. Conclusions: With the aim of preventing suicide, greater efforts should be made to combat the persisting stigmatizing attitudes displayed towards mental disorders and suicide itself . Indeed, the role of stigma as a risk factor for suicide should further motivate and spur more concerted efforts to combat public stigma and support those suffering from perceived or internalized stigma. Experts and scientific societies should form an alliance with the media in an effort to promote a marked change in the societal perception of mental health issues and suicide. As stigma may result in severe consequences, specialist care and psychological interventions should be provided to populations submitted to stigma